2007
DOI: 10.1176/appi.ajp.2007.06122030
|View full text |Cite
|
Sign up to set email alerts
|

History of Past Sexual Abuse in Married Observant Jewish Women

Abstract: While observant Jewish women live in a culture defined by a high degree of adherence to specific laws of conduct, including rules designed to regulate sexual contact, sexual abuse of various types still exists among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
2
28
2
Order By: Relevance
“…Moreover, the women who had never told often had suffered the most serious abuse. Recent research in the Orthodox community found results consistent with this research; only 35 percent of sexual abuse survivors who filled out an anonymous questionnaire at the mikvah, the ritual bath, had ever disclosed the abuse to anyone before reporting it on the anonymous survey (Yehuda et al, 2007).…”
Section: Delayed Disclosuresupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, the women who had never told often had suffered the most serious abuse. Recent research in the Orthodox community found results consistent with this research; only 35 percent of sexual abuse survivors who filled out an anonymous questionnaire at the mikvah, the ritual bath, had ever disclosed the abuse to anyone before reporting it on the anonymous survey (Yehuda et al, 2007).…”
Section: Delayed Disclosuresupporting
confidence: 73%
“…The study by Rachel Yehuda et al (2007) found that the rate of abuse in that sample of Orthodox women was higher among those who, although religious today, had not grown up in observant homes, suggesting that some survivors may seek Orthodoxy in order to find comfort away from a previous life of abuse. Against these findings is some very convincing anecdotal literature reporting on cases of abuse victims who have left, either partially or entirely, the confines of religious communities in a rebellious strike against their abusers and their community's complicity (Winston, 2005).…”
Section: T H E a Du Lt S U Rv I Vormentioning
confidence: 95%
See 1 more Smart Citation
“…After completion of our study, Yehuda et al [19] reported on CSA in a nonclinical sample of orthodox Jewish women in the USA. Of 380 women answering an advertisement to respond to a questionnaire, 26% reported sexual abuse, 16% before the age of 13.…”
Section: Tablementioning
confidence: 99%
“…These rates of CSA were similar to those we found in psychotic women in Israel. The subjects of Yehuda et al [19], although Jewish, were studied with a different methodology and other variables prevent definitive comparison. Further research on CSA and psychosis requires designs that can differentiate between CSA as a result of pre-psychotic disturbances within a family versus CSA as a causative factor in psychosis.…”
Section: Tablementioning
confidence: 99%